SAFE SPACE FOR FEMALE PILGRIMS WITHOUT A MAHRAM DURING THE PERFORMANCE OF UMRAH - Salsabila, Afria Putri; Rozaq, Abdul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The Saudi Arabian government's policy of allowing women to perform Umrah without a mahram since 2022 marks a significant change. However, this raises an urgent need for a comprehensive security system. This study aims to analyze the concept and implementation of a safe space for female pilgrims without a mahram during the Umrah pilgrimage, viewed from a legal, social, and spiritual perspective. This descriptive-analytical qualitative study employs three main data collection techniques: in-depth interviews for primary data, documentation studies and policy analysis for secondary data, and field observations. Data validity was tested using source triangulation. The results show that a safe space is formed through three key elements: (1) Policy and technology, namely implementing gender-based segregation of worship areas and the use of nusuk applications and GPS trackers as a substitute for the protective function of mahrams, (2) Social and collectivity such as the formation of solidarity and formal and informal mentoring networks among female pilgrims, (3) Spiritual and Autonomy providing the availability of a worship environment that supports devotion and spiritual independence. The construction of this safe space aligns with the principles of maqāṣid al-syarī'ah, particularly in safeguarding the body and soul (ḥifẓ al-nafs). This study recommends strengthening technology- based security systems, developing specific guidance for assistance, and improving digital literacy for pilgrims.